The Effectiveness of Wayground Application in Enhancing Grammar Mastery of Students with Different Motivation - Azizah, Siti Nor; Setiaji, Arso; Susanto, Dias Andris (Universitas PGRI Semarang, 2025)
Grammar mastery is one of the most essential components in English language proficiency. However, However, many EFL students often deal with tenacious learning difficulties. They take place due to monotonous learning instructions and students’ different learning motivation. The academic research examines the effectiveness of Wayground (formerly Quizizz) in increasing students’ grammar mastery across varying levels of learning motivation. By using a quasi-experimental mixed-method design, the research involved 70 eleventh-grade students at SMA Negeri 1 Pecangaan, Jepara. They were assigned to an experimental group receiving instruction through Wayground and a control group receiving conventional methods. The research data were gathered through assessments of grammar mastery administered as pre-test and post-test, a questionnaire of learning motivation adapted from Gardner’s Attitude/Motivation Test Battery, and a questionnaire of student perception. Quantitative data were analysed using paired-sample t-tests, independent-sample t-tests, and two-way ANOVA. Qualitative data served to enrich and support the interpretation of the findings. The results indicate that both instructional approaches led to significant improvements in students’ grammar mastery. The experimental class achieved a higher mean gain score than the control class but the difference was not statistically significant. Furthermore, learning motivation and the interaction between instructional method and motivation did not have significant effect on grammar mastery improvement. Nonetheless, students reported positive perceptions of Wayground, principally regarding increased engagement, enjoyment, and the provision of immediate feedback. These findings suggest that Wayground represents a pedagogically beneficial supplementary tool for grammar instruction, especially for boosting active and enjoyable learning experiences in EFL classrooms.